The five people you meet in heaven - Albom, Mitch, 1958- (New York : Hyperion, 2003)
Killed in a tragic accident, Eddie, an elderly man who believes that he had an uninspired life, awakens in the afterlife where he discovers that heaven consists of having five people explain the meaning of one's life.
780
Accelerated Reader AR
Keywords: Accident victims -- Fiction; Amusement parks -- Fiction; Amusement rides -- Fiction; Future life -- Fiction; Older men -- Fiction; Heaven -- Fiction; Death -- Fiction; Accident victims -- Fictional Works; Amusement parks -- Fictional Works; Amusement rides -- Fictional Works; Future life -- Fictional Works; Aged men -- Fictional Works; Heaven -- Fictional Works; Death -- Fictional Works; Psychological fiction